2020
DOI: 10.1155/2020/5480614
|View full text |Cite
|
Sign up to set email alerts
|

Studying and Optimizing the Effect of Process Parameters on Machining Vibration in Turning Process of AISI 1040 Steel

Abstract: The turning, which consists of the removal of metal from the outer diameter of a rotating cylindrical workpiece, is one of the most common techniques for cutting, especially when finishing the product. The values of the cutting parameters, such as feed rate, cutting speed, and depth of cut, in a turning operation must be selected carefully to improve the profit of operations by enhancing productivity and reducing the total manufacturing cost for each component. A high vibration leads to poor surface finish and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In turning of AISI 1040 steel, the vibration increases as the a , v and f increase. 30 In cool conditions, the vibration value is the lowest in cutting number 2 (with cooling liquid). This is because the use of coolant reduces friction between the tool and the workpiece.…”
Section: Resultsmentioning
confidence: 97%
“…In turning of AISI 1040 steel, the vibration increases as the a , v and f increase. 30 In cool conditions, the vibration value is the lowest in cutting number 2 (with cooling liquid). This is because the use of coolant reduces friction between the tool and the workpiece.…”
Section: Resultsmentioning
confidence: 97%
“…Tese experimental designs were developed using the Design-Expert v12 software, which is a tool that helps us in designing experiments and analyzing the data. To anticipate spindle and worktable vibration, a second-order mathematical equation was devised, whose appropriateness was determined using ANOVA [31,32]. Te MATLAB software was used for vibration optimization experiments.…”
Section: Experimental Designmentioning
confidence: 99%
“…In this context, 100 mm in diameter and 250 mm in length tempered steel samples were used. 1,[36][37][38][39][40] This steel material used extensively in most industry for a wide range of application such as; rotating machinery parts and components, crank shafts, motor shafts, axle shafts, pump shafts and railway locomotive traction motors shaft due to vibration behaviors. 1 The cutting tool of TNGA (TiN-Al 2 O 3 ) AB20 120408 T01020 and MTJNL 2525 M1604 model of tool holder were used in experimental study.…”
Section: Experiments Materials and Ceramic Cutting Toolmentioning
confidence: 99%
“…37 In an experimental study, it was investigated the effects of machining parameters in turning process of AISI 1040 steel. 38 In another study, it was studied the machining parameters and their effect on the Ra of steel samples machined under dry and wet turning conditions. Results revealed that, Ra is highly affected by the machining parameters and also the cooling conditions.…”
Section: Introductionmentioning
confidence: 99%